Investigating the Outcomes of the Military Wing of The Civil Society in Enforcing Democracy or Cessation: Case Study: Burkina Faso and Cameroon - Evaristus, Agberndifor (Advances in Social Sciences Research Journal, 2020)
In Hobbes’ Leviathan, he portrays man as a rationally angry and dangerous creature capable of hurting another in order to remain alive. He says human interpersonal relations are mostly characterized by brutality in what he called “Man against man” in order words man is another man’s wolf. According to him human interpersonal relations are substantiated by the fear of bad or sudden death and so, every human seeks for ways to either remain alive or to maintain his status quo. Anger, resentments, protests and violence are clearly part of the human life and one of the reasons every human must be careful to gather his human arsenal in order to deter another from killing him. Man cannot in any way deal with the other without these ingredients ever present in interpersonal human relations. Though pejorative with many negative defects as Hobbes sees it, they have also brought some common good to societies and countries whose governments are experts in crisis management. However, the same is not the case for countries with haughty governments ruled by mostly dictatorships, which underrate their citizens and use the military to deter them from fighting for their rights. This article shall seek to firstly understand the conceptual background of civil society by examining different definitions of what it means. Secondly, it shall look at two fundamental factors that make civil societies very important and powerful for state development as well as destruction, however, will discuss them separately as one will be deeply discussed in the later parts of the study. Thirdly, it shall shallowly review the relationship between the civil society and democracy in Nigeria which will serve as a preview to understand the foreseen projection that the civil society and democracy in tandem engenders development. Secondly, at the core lies the tireless and selfless service of a powerful civil society vis-à-vis to maintain social order, unity, and social cohesion as well as keep the spirit of nationalism aflame. Lastly, this article shall concentrate on the most vital part of the study which is the military wing of civil societies. This study will show that when the civil society organization is pushed to its limits, it has the power to bring no small trouble to their host governments and domestic affairs sometimes crossing international boundaries and leading to serious international security issues and humanitarian crises. To fully understand this part, the study shall stroll through political exclusion, isolation, opportunity, greed and violence as possible incentives to arouse the devastating military wing of the civil society. Furthermore, the most comprehensive and elaborate study to use to explain this will be the analysis of Collier and Hoeffler’s account of civil war studies but this will be mentioned in passing. To avoid auto repetition, an article earlier published by me titled “Investigating the causes of civil wars in Sub-Saharan Africa, Case study: South Sudan and the Central African Republic” shall be cited. More so, this study shall look at carefully localized independent and dependent variables which shall be used in the comparative method to review the verifiable effects of the military wing of the civil society in Cameroon and Burkina Faso. “When the enabling factor fails to a haughty government, then civilian enacted military action is the only solution. However, the effects of this civilian enacted military action differs from place to place and there is no assurance of how positively democratic or devastating they could be” The independent variables shall be political isolation, political exclusion and polarization. And the dependent variable shall be the democracy and secession.